2015
DOI: 10.1007/s12262-015-1268-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Oral Nutritional Supplement Containing Arginine, Glutamine, and Hydroxymethylbutyrate (Abound®) on Healing of Colonic Anastomoses in Rats

Abstract: We evaluated the effects of the oral nutritional supplement containing arginine, glutamine, and hydroxymethylbutyrate (Abound®) on healing of colonic anastomoses in experimental rat model. Seventy WistarAlbino male rats were divided into seven groups. Colon transection and anastomosis were performed in all groups except for the sham group. In groups 2 and 5, rats were fed with standard rat chow after the operation. Oral nutritional supplement was added to standard nutrition for 3 days postoperatively in group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Eleven studies assessed their outcomes on only one time point, of which two [ 10 , 16 ] within the first 4 days after surgery (a), and nine [ 4 , 5 , 13 , 19 , 22 , 26 , 29 , 32 , 37 ] on day 5 or later (b). Eight studies [ 7 , 27 , 28 , 30 , 32 , 33 , 38 , 39 ] performed outcome assessments in both time frames (a, b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies assessed their outcomes on only one time point, of which two [ 10 , 16 ] within the first 4 days after surgery (a), and nine [ 4 , 5 , 13 , 19 , 22 , 26 , 29 , 32 , 37 ] on day 5 or later (b). Eight studies [ 7 , 27 , 28 , 30 , 32 , 33 , 38 , 39 ] performed outcome assessments in both time frames (a, b).…”
Section: Resultsmentioning
confidence: 99%
“…This relative increase in mature collagen in the anastomosis was still present at 14 days after index surgery. Other studies that found an effect of butyrate administration on collagen deposition in anastomoses were the studies from Yaman (2012) [ 40 ] and Kusabbi (2015) [ 33 ]. In both studies an increase in collagen deposition in the anastomotic area was observed after a daily (before and/or after surgery) administration of AGHMB, a butyrate based oral nutritional supplement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations